Blood, faith and iron : a dynasty of Catholic industrialists in sixteenth- and seventeenth-century England - Belford, Paul, (Archaeopress archaeology., 2018)
An iconic industrial landscape, presented as the birthplace of the Industrial Revolution and so part of a national narrative of heroic Protestant individualism. However this is not the full story. In fact this industrial landscape was created by an entrepreneurial Catholic dynasty over 200 years before the Iron Bridge was built.